Space plasma physics : School and Workshop on Space Plasma Physics, Sozopol, Bulgaria, 31 August-7 September 2008 - School and Workshop on Space Plasma Physics (2008 : Sozopol, Bulgaria); Zhelyazkov, Ivan; United States. Air Force. European Office of Aerospace Research and Development (Melville, N.Y. : American Institute of Physics, 2009)
Includes bibliographical references and index